Literary Reputation of S. Dovlatov and Ven. Erofeev as the Result of Publishing Practices (Based on the Material of the Russian Publishing Market 1990–2010) - V. Yu. Bal; O. I. Belova; A.-M. A. Shpilko (Библиосфера, 2024)
The relevance of the article is associated with the increased interest of modern humanitarian thought in the problems of the sociology of literature, literary reputation and the need to identify possible forms and methods of forming the symbolic authority of writers in the postclassical era. The aim of the article is consider the principles of formation of the posthumous literary reputation of S. Dovlatov (1941–1990) and Ven. Erofeev (1938–1990) on the material of domestic publishing practices 1990s–2010s and memoirs about them. The institute of publishers is presented as an agent of influence on the posthumous literary reputation of writers who have been returned to the Russian cultural space in the first post-soviet decade. The article considers literary reputation in a historical, dynamic and procedural way. The analysis of the material (year and type of editions, circulations, reputations of publishers and compilers) makes it possible to identify both the semantic dynamics of the reputation fields around the figures of the writers in question in the chronological framework indicated and the principles of domestic publishing practices that influence the writers’ reputation. The results of the study suggest that on the background of general dynamics of transformation of the domestic publishing market in the 1990–2000s changes in publishing strategies are observed in the publication of the literary heritage of  returned writers’names and memoirs and biographical literature about them.